Makna Kata Jancok dalam Film “Yowis Ben 2” - Santo Santo; M Abdul Ghofur (Jurnal Nomosleca, 2021)
Among several films made in Indonesia, there are some films that convey a good message. Through the film "Yowis Ben 2", the director tries to make something new and different from the comedy genre films from previous films. The purpose of this research was to know and understand the meaning of communication behavior in the film "Yowis Ben 2".This study used a qualitative research method using the object of research the film "Yowis Ben 2". Then the data analysis technique used the semiotic analysis technique of Roland Barthes which is based on meaning through signs. The model shows the three main elements forming the sign of denotation, connotation, and myth. The results of this study indicated that the word Jancok in the film "Yowis Ben 2" has three different meanings, an expression of anger and resentment, an expression of surprise, and an expression of happiness. So that the meaning of the word Jancok has different meanings depending on one's communication behavior and on certain conditions and situations. The messages in communication behavior were understood from various sides and through the signs that appear both visual and verbal. That is where the meaning of the word in communication behavior is related to the expression in the film. It can be concluded that the characters and the conversations that exist in each scene have meaning from the behaviors and expressions. Keywords: Meaning of the Word “Jancok”, Film, Semiotic AnalysisDOI : https://doi.org/10.26905/nomosleca.v7i1.5634